(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Biscuits are ready-to-eat nutritious baked snacks that are available in different shapes and sizes. One of the problems that militate against food security in developing countries such as Nigeria is postharvest loss and underutilization of locally cultivated food crops. This study aimed at evaluating the quality of biscuits produced from wheat, tiger nut and orange fleshed sweet potato flours. Wheat flour was substituted with tiger nut and orange fleshed sweet potato (OFSP) flours for the production of biscuits. While constant 10% tiger nut flour was used in each of the six formulations, the OFSP flour portions were increased from 5 to 30%. A 100% wheat flour served as control. The functional properties of the flours, proximate composition, energy value, vitamin contents, physical and sensory properties of the biscuits were determined using standard methods. The result of the functional properties showed no significant differences (p>0.05) in the bulk densities and gelatinization temperatures of the flour blends. There was significant (p<0.05) reduction in the moisture content of the biscuit samples made from the composite flours compared to the control biscuit sample. Inclusion of tiger nut and sweet potato flour led to increase in the fat, fibre, carbohydrate content and energy values of the biscuit samples. The pro-vitamin A and vitamin C increased as the proportion of orange sweet potato increased and in all the composite biscuits containing tiger nut flour. There were no significant differences (p>0.05) in the thickness, spread ratio and volume of the biscuits. The results of the sensory properties